Demand for modern contraceptives and use among women of reproductive age in north central Nigeria - Akpoti, Okehi O.; Kareem, Abiodun J.; Kareem, Adesola O.; Ogunromo, Ayodele Y.; Owoeye-Lawal, Oluwatosin T.; Ahmed, Liasu A.; Akinyugha, Akintunde O.; Bewaji, Temitayo O.; Babalola, Emmanuel O.; Orji, Eloho J.; Atimoh, Charles O.; Ibekwe, Ogechukwu C. (International Journal Of Community Medicine And Public Health, 2023)
Background: The maternal mortality rate in north central Nigeria remained unacceptably high and the use of modern contraceptives among women of reproductive age in north central Nigeria may be a way of reducing maternal death. The study aimed to determine the contraceptive uptake among women of reproductive age in north central Nigeria and the factors that influence the use of contraceptives. Methods: The study was a secondary analysis of 2018 national demographic and household survey data. Data were abstracted for women of reproductive age 15-49 years across seven states in Nigeria. Results: The level of awareness of modern contraceptives was 91.6% while the modern contraceptive prevalence rate was 38.8% and current contraceptive prevalence use was 53.4%. The main source of information was radio 298 (22.4%) and the most common contraceptive used was implants 81 (29.3%) followed by hormonal contraceptive injections 77 (27.4%). The factors associated with the use of contraceptives include the age of the women, religion, level of education, number of children ever born, and partners’ opinion (p=0.001). The proportion of women who oppose contraceptive use was significantly higher (χ2=4.732, p=0.030). Similarly, the proportion of women whose husbands/partners opposed contraceptive use was significantly higher (χ2=8.589, p=0.003, OR=3.2). Conclusions: The prevalence of contraceptive use is low in north-central Nigeria despite the high level of awareness. There is a need to involve the women’s partner to increase the uptake of contraceptive use.